(untitled) (International Journal of Environmental Sciences, 2025)
Entrepreneurship is essential for the overall development and progress of any country. Recently, the importance in women has increased significantly due to the increased empowerment and gender equality. Each day, we discover another account of a woman who has triumphed against traditional gender norms and ventured into the realm of entrepreneurship. The objective of the present investigation is to ascertain the impact of government policies regarding women’s business in the region pertaining to Jammu and Kashmir. The research utilized aExplanatory report research methodology. The research found 379 women entrepreneurs who were efficiently managing their firms utilizing a non-probability convenient sampling approach. A questionnaire was issued to collect data, which was then subjected to various statistical analyses using SPSS and AMOS software. Percentages and means were used to examine the data. According to the results, the researchers establishing that the respondents had a modest degree of knowledge of government policies. They recommended that government organizations should arrange camps to educate women about the positive aspects of entrepreneurship.